Reframing health and health policy in Ireland : a governmental analysis - Edwards, Claire; Fernández, Eluska (Manchester History of Medicine, 2017)
This text seeks to deepen our theorization of Irish health policy agendas and practices by demonstrating how governmentality can be used to understand some of Ireland's contemporary health issues and dilemmas. Drawing on a range of empirical contexts, it explores the potential of governmentality to contribute to a critical politics of Irish health and health policy.